Comprehensive Review of The Intersection Between Radiology and Dentistry in Patient Care - Asiri, Hanan Ali Ahmad; Asiri, Reem Ahmed; Aseri, Malak Ahmed Moufareh; Alahmari, Reem Mohammed; Alasmri, Shahd Ali; Alshahri, Mona Nooh; Dokman, Abdullah Mohammed; AlAhmari, Bashair Abdullah; alrufaidy, Waad Mohammed; Aljabir, Kholoud Ali (Journal of Ecohumanism, 2024)
Radiology and imaging are some areas where rapid strides have been made, thus contributing to diagnostic and therapeutic medicine. The detection of a specific pathology or disease or therapeutic intervention has required high precision. Whether it is simple X-ray or computed tomography scans, ultra-modern functional MRI scans, molecular imaging, and more, radiology has been through lots of improvements to enhance clinicians’ ability to make more accurate clinical decisions. This review aims to discuss the role of radiology throughout the years and specify the contemporary usefulness of these methods, using diagnosis and therapy as key aspects. In addition, the review highlights certain issues related to implementing these technologies in practice, such as costs, availability, and staff education. We also evaluate how these novelties contribute to patient benefit today and in the future or can lay the foundation for individualized treatment.